Pengaruh Dukungan Teman Sebaya Terhadap Prokrastinasi - Keisyah Nadya Zahroh; Dhieta Rizky Palupi Prameswari; Risma Anita Puriani (INDO PUBLISHING, 2026)
Delaying school responsibilities is a common behavior among students, known as academic procrastination, which can adversely impact their performance and mental health. This research seeks to examine how peer support influences academic procrastination in students by analyzing previous studies. A descriptive literature review of several pertinent scientific articles has been utilized for this purpose. The findings reveal that peer support significantly affects students' academic procrastination. Supportive peers who provide motivation, engage in collaborative learning, and offer emotional backing can help lessen students' procrastination. On the other hand, negative peer surroundings can lead to an increase in procrastination behaviors. Furthermore, aspects like motivation for learning, self-discipline, and effective time management also play a role in either reinforcing or diminishing this connection.In summary, peer support is a crucial element in helping students combat academic procrastination. It is, therefore, essential to foster a positive peer atmosphere in educational settings